PENGARUH DESENTRALISASI, STRATEGI BISNIS, DAN PEMANFAATAN SISTEM INFORMASI AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL (STUDI EMPIRIS PADA PERUSAHAAN BUMN DI BANDA ACEH) - Islami, Qari Nur; Daud, Rulfah M. (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to (1) Analyze the effect of decentralization on managerial performance, (2) Analyze the effect of business strategy on managerial performance, (3) Analyze the effect of broad scope on managerial performance, (4) Analyze the effect of timeliness on managerial performance, (5) Analyze the effect of aggregation on managerial performance, (6) Analyze the effect of integration on managerial performance, (7)Analyze the effect of decentralizatiion, business strategy, broad scope, timeliness, aggregation, and integration on managerial performance. The population of this research is top manager and middle manager to 83 managers who had been set as sample in 22 companies. This study uses primary data with data collection techniques were collected by distributing questionnaires at BUMN companies. Statistical tests are performed using multiple linear regression analysis with SPSS version 22. The results of this study prove that the decentralization, broad scope, timeliness, aggregation, and integration have a significant possitive effect on managerial performance. Business strategy have not effect on managerial performance.